McGovern nipple: An alternative for nose breathing in newborn with CHARGE syndrome, having bilateral choanal atresia - Sanjay Kumar (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2020)
CHARGE syndrome caused by the mutation of CHD7 genes is associated with many congenital anomalies. Individuals are diagnosed based on major and minor characteristic features and confirmed by genetic testing. Major criteria characterized by 4C's: Coloboma, Cranial nerve abnormalities, Choanal atresia, and typical CHARGE ear are seen. In this article, a case of a newborn suffering from CHARGE syndrome having stressful breathing is reported. A McGovern nipple was fabricated and secured in the oral cavity to maintain the oral airway till further surgical interventions were done.